The ABA392/pET30a protein of Pasteurella multocida provoked mucosal immunity against HS disease in a rat model - Kang, Tzin Lim; Velappan, Rita Devi; Kabir, Nurul; Mohamad, Jamaludin; Rashid, Nurshamimi Nor; Ismail, Salmah (Elsevier, 2019)
Haemorrhagic septicaemia (HS) is a well-known high fatality septicaemic disease happening among bovines. The disease is caused by the Pasteurella multocida serotype B:2 bacteria. P. multocida B:2 has high mortality and morbidity rates and is spread through the intranasal and oral routes in bovines. In this study, our aim was to investigate the efficacy of the recombinant protein vaccine, ABA392/pET30a via intranasal inoculation by targeting the mucosal immunity. The constructed recombinant protein vaccine ABA392/pET30a was subjected to an animal study using Sprague Dawley rats. The study was divided into two parts: active and passive immunization studies. Both studies were carried out through the determination of immunogenicity (using Total White Blood Cell (TWBC) Count with Indirect ELISA) and histopathogenicity, analyzing (Bronchus Associated Lymphoid Tissue (BALT) formation) in lungs. As a result, the IgA and IgG development of both tested groups: group 1 (50μg/mL protein vaccine) and group 2 (100μg/mL protein vaccine) showed equivalent with the positive control group 4 (formalin-killed P. multocida B:2). However, there was a significant difference when compared with the negative control group 3 (normal saline). These results demonstrate that both the protein vaccine at the concentration 50μg/mL and 100μg/mL have the same efficacy as the commercially available positive control vaccine. From the studies, higher concentration of protein vaccine at 100μg/mL showed higher development of both IgA and IgG compared to 50μg/mL protein vaccine. Higher and rapid development of IgA compared to IgG showed that mucosal immunity has been induced through the intranasal administration of the protein vaccine. In addition, leucocytosis was observed at each dose of vaccination showed that the protein vaccine is capable to induce the immune responses of the host. Histopathogenicity studies of the vaccinated groups showed more BALT formation and no severe lesions after challenge compared to the negative control group. Besides, no inflammatory onsite or anaphylactic responses were observed after the intranasal inoculation which proved to be safer and provided longer lasting immunity. Therefore, recombinant protein vaccine ABA392/pET30a could be a potential candidate for intranasal administration which can provoke mucosal immunity against HS disease.